Attitudes toward older people among nursing students in Greece. Issue 6 (29th October 2022) - Fradelos, Evangelos C.; Artemi, Sofia; Tsalogidou, Areti; Almpani, Eleni; Malli, Foteini; Lavdaniti, Maria; Papathanasiou, Ioanna V.; Tzavella, Foteini
Abstract: Background: The age profile of the population has shifted globally. Age discrimination has been documented, particularly in the areas of health and employment. Aim: This study aims at examining nursing students' attitudes toward older people and dehumanization of older people among nursing students. Methods: A cross‐sectional design was employed in this study. A structured questionnaire was used to collect data, which included a sociodemographic variables questionnaire, the Kogan's Attitude towards Old People Scale (KAOP) scale, a modified version of the Human Nature & Human Uniqueness Scale, the Ten‐Item Personality Inventory (TIPI) and the Toronto Empathy Questionnaire. A total of 410 undergraduate nursing students participated in this study. Descriptive statistics were applied while inferential statistics such as Pearson correlation, and regression analysis with the stepwise method were also performed. The significant level was set as p  ≤ .05. SPSS‐25 was used for the analysis of data. Results: The total mean score of the KAOP scale was 128.84 ± 14.32, indicating that nursing students had a slightly positive view of older individuals. Nursing students scored higher on the mechanistic dehumanization scale than on the animalistic dehumanization one. A strong negative association was found between Mechanistic and Animalistic dehumanization with the KAOP scale and empathy. Year of study, age, and gender were identified as predictor variables for mechanical dehumanization. Conclusion: Personality traits, demographic variables, and nursing students' level of empathy are factors that influence their views about older people and the dehumanization of older people.